Pengaruh Azo Terhadap Histopatologis Kandung Kemih Tikus Pada Bahan Biologis Tersimpan - Hafny Afna Salsabilla; Sadeli Masria; Meike Rachmawati (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. Congo Red is a synthetic azo dye used in the textile industry with potential urogenital toxicity, linked to bladder cancer via its benzidine metabolites. This retrospective analytic observational study aimed to evaluate the subchronic toxicity of Congo Red on the histopathology of Wistar rat urinary bladders. A total of 28 tissue samples were divided into four groups: control, doses of 190 mg/kgBW, 375 mg/kgBW, and 750 mg/kgBW. Evaluations were performed using Hematoxylin-Eosin staining and a scoring system. Results showed no histopathological changes (score 0) in the control, 190, and 375 mg/kgBW groups. In the 750 mg/kgBW group, mild hyperplasia was observed in 28.6% of samples (score 1). The Kruskal-Wallis test yielded p=0.101 (p>0.05), indicating no significant difference among groups. In conclusion, subchronic exposure to Congo Red has not caused significant toxic effects on the urinary bladder. Future studies with longer exposure durations and higher doses are needed to assess its long-term carcinogenic potential. Abstrak. Congo Red adalah pewarna sintetis azo dalam industri tekstil yang berpotensi toksik terhadap organ urogenital dan memicu kanker kandung kemih melalui metabolit benzidine. Penelitian observasional analitik retrospektif ini bertujuan mengevaluasi efek toksisitas paparan subkronis Congo Red terhadap histopatologi kandung kemih tikus Wistar. Sebanyak 28 sampel jaringan dibagi menjadi empat kelompok: kontrol, dosis 190 mg/kgBB, 375 mg/kgBB, dan 750 mg/kgBB. Evaluasi menggunakan pewarnaan Hematoxylin-Eosin dan sistem skoring. Hasil menunjukkan kelompok kontrol, dosis 190, dan 375 mg/kgBB tidak mengalami perubahan histopatologis (skor 0). Pada dosis 750 mg/kgBB, ditemukan hiperplasia ringan pada 28,6% sampel (skor 1). Uji Kruskal-Wallis menunjukkan nilai p=0,101 (p>0,05), yang berarti tidak ada perbedaan bermakna antar kelompok. Kesimpulannya, paparan subkronis Congo Red belum memberikan efek toksik signifikan pada kandung kemih. Penelitian lanjutan dengan durasi paparan dan dosis lebih tinggi diperlukan untuk menilai potensi karsinogenik jangka Panjang.